Bio-inspired optimisation for economic load dispatch: a review. (1st January 2014) - Dubey, Hari Mohan; Panigrahi, Bijaya Ketan; Pandit, Manjaree
Restructuring of power sector in the last decade has introduced competition among the various entities of power system. In this revolutionised competitive environment, day by day increase in fossil fuel cost along with the environment issues, force the electric power producing utilities for a best possible economic real power dispatch with a minimum power production cost. The economic load dispatch (ELD) is a complex optimisation problem due to non-linear, non-convex type fuel cost characteristics of the fossil fuel operated thermal generators. Although many conventional optimisation approaches have been developed to solve such problem, over the past decade, the bio-inspired optimisation (BIO) techniques have shown promising performance on such constrained ELD problems. This paper attempts to provide a comprehensive review of application of BIO algorithms to solve most complex practical ELD problems.